PERFORMANCE OF GILLNET-MESH SIZE SELECTIVITY FOR THREE FLYINGFISH SPECIES IN AMBON WATERS, MOLUCCAS PROVINCE - Hutubessy, Barbara Grace; Syahilatua, Augy (Marine Research in Indonesia, 2010)
The gillnets performance for capturing flying fish was obtained from the selectivity parameters of each mesh size. Gillnet selectivity parameters for flying fish were estimated using multi-panel drift gillnets with four different mesh sizes in southern Ambon Island. The black-spot flying fish Cheilopogon suttoni reached peak selectivity at 20.34 cm for mesh size of 1.25", 24.37 cm (1.5") and 28.47 cm (1.75"). Peak selectivity occurred at 22.16 cm for the 1,25" mesh size in the yellow-spot flying fish Cheilopogon abei, with the maximum size selectivity at 31.61cm for the 1.75" mesh. The optimum size for the black-plain flying fish Hirundichthys oxycephalus was 18.67 cm for the 1.25" mesh size, and 22.37 cm for 1.50" mesh size. Selectivity was highest at 26.12 cm for the 1.75" mesh size. Gillnet used in this study was constructed specifically for targeting flying fish suggesting that information on mesh selectivity examined here should has direct applicability to local flying fish fishery.